The Impact Of Current Reforms On Income Distribution In Peru - Figueroa, Adolfo (1973)
The objective of this work is to use the Peruvian case to exemplify some practical problems the redistribution policies impose. First, which can be the effectiveness of redistribution policy to increase the income of the poorest quartile of the population? Do we need to abandon redistribution because it is ineffective and it will only redistribute poverty? Second, which is the technical possibility to reach the poor? In this sense this work hast the pretension to go beyond the concrete case that it examines, the Peruvian case, to extract general conclusion of this experience.